(untitled) (Scientia Agropecuaria, 2025)
Root-knot nematodes (RKNs) are classified under the genus Meloidogyne and are among the most devastating pests affecting strategical agricultural crops. They attack a wide variety of plant species, including vegetables, fruit trees and ornamental plants, causing root deformities and even lead to plant death in severe cases of infestation. These nematodes contribute to substantial crop yield loss and affect the quality of harvested products. Although synthetic nematicides are available for the control of these pest organisms, there is a growing emphasis on exploring sustainable and eco-friendly alternatives, such as nematophagous fungi like the genera Purpureocillium, Arthrobotrys, Dactylellina, Orbilia, and Trichoderma, among others. Here a review of literature on the matter is given, with a focus on the taxonomic classification of the most relevant fungal orders and genera, their diagnostic features, mechanisms of action, and potential as biological control agents (BCAs) against Meloidogyne species. Other relevant aspects addressed in this review include a brief description of the nematode genus Meloidogyne, along with the symptoms it causes in host plants, such as root gall formation, stunted growth, and yellowing of foliage, among others. It also describes integrated pest management (IPM) strategies such as crop rotation, resistant crops, soil solarization, trap crops, as well as currently used chemical control techniques. Biological control alternatives are also presented with particular emphasis on nematophagous fungi. Future research should focus on improving the formulae of biological agents based on nematophagous fungi under field conditions and understanding their ecological roles and interactions in soil microbiomes.